Microglial Activation – Tuning and Pruning Adult Neurogenesis - Ekdahl, Christine T (Frontiers in Pharmacology, 2012)
New neurons are continuously generated in two adult brain regions: the subgranular zone of the hippocampus and the subependyma by the lateral ventricles, referred to as the neurogenic niches. During their development from neural stem cells to mature functionally integrated neurons numerous choices are made, such as proliferation or quiescence, cell survival or death, migration or establishment, growth or retraction of processes, synaptic assembly or pruning, or tuning of synaptic transmission. The process is altered by physiological stimuli as well as several brain diseases. Microglia are located within the neurogenic niches and have become interesting candidates for modulating neurogenesis in both the healthy and injured brain. They become activated by foreign antigens or changes in the brain homeostasis and transform this innate immunity into an adaptive immune response by recruiting systemic immune cells. Most studies report an acute decrease in the survival of new neurons following this classically activated microglia reaction. The long-term effects are more complex. In neurodegenerative diseases, microglial activation is more heterogeneous and the transformation from a pro- to an anti-inflammatory cytokine profile and the deactivation of microglia is not well defined. The diversity is reflected by numerous reports describing both beneficial and detrimental effects on neurogenesis, primarily on the proliferation, survival, and cell fate. However, relatively few studies have investigated alterations at later stages of neurogenesis including the functional integration. Though likely, it is not established how a fine-tuned cross-talk between microglia and adult-born neurons would work and how it changes upon microglia activation. This review will therefore launch three hypotheses for how microglia might direct synaptic integration of newborn neurons, currently a fast expanding research field.